Beneficial bombing the progressive foundations of American air power, 1917-1945 - Clodfelter, Mark (Studies in war, society, and the military, 2010)
The Progressive Era, marked by a desire for economic, political, and social reform, ended for most Americans with the ugly reality and devastation of World War I. Yet for Army Air Service officers, the carnage and waste witnessed on the western front only served to spark a new progressive movement -to reform war by relying on destructive technology as the instrument of change. In Beneficial Bombing Mark Clodfelter describes how American airmen, horrified by World War I s trench warfare, turned to the progressive ideas of efficiency and economy in an effort to reform war itself, with the heavy bomber as their solution to limiting the bloodshed. They were convinced that the airplane, used as a bombing platform, offered the means to make wars less lethal than conflicts waged by armies or navies. Clodfelter examines the progressive idealism that led to the creation of the U.S. Air Force and its doctrine that the finite destruction of precision bombing would end wars more quickly and with less suffering for each belligerent. What is more, his work shows how these progressive ideas emerged intact after World War II to become the foundation of modern U.S. Air Force doctrine. Drawing on a wealth of archival material, including critical documents unavailable to previous researchers, Clodfelter presents the most complete analysis ever of the doctrinal development underpinning current U.S. Air Force notions about strategic bombing.